The Relationship of Assisted Reproductive Technology on Perinatal Outcomes in Triplet Gestations - Shah, Jaimin S.; Roman, Tania; Viteri, Oscar A.; Haidar, Ziad A.; Ontiveros, Alejandra; Sibai, Baha M. (American Journal of Perinatology, 2018)
Objective To assess whether assisted reproductive technology (ART) is associated with increased risk of adverse perinatal outcomes in triplet gestations compared with spontaneous conception.Study Design Secondary analysis of a multicenter randomized trial for the prevention of preterm birth in multiple gestations. Triplets delivered at ≥ 24 weeks were studied. The primary outcome was the rate of composite neonatal morbidity (CNM) that included one or more of the following: bronchopulmonary dysplasia, respiratory distress syndrome, necrotizing enterocolitis, culture proven sepsis, pneumonia, retinopathy of prematurity, intraventricular hemorrhage, periventricular leukomalacia, or perinatal death.Results There were 381 triplets (127 women) of which 89 patients conceived via ART and 38 patients spontaneously. Women with ART were more likely to be older, Caucasian, married, nulliparous, have higher level of education, and develop pre-eclampsia. Spontaneously conceived triplets were more likely to delivery at an earlier gestation (31.2 ± 3.5 vs 32.8 ± 2.7 weeks) (p = 0.009) with a lower birth weight (p < 0.001). After adjusting for confounders, no differences were noted in culture proven sepsis, perinatal death, CNM, respiratory distress syndrome, or Apgar score < 7 at 5 minutes. All remaining perinatal outcomes were similar.Conclusion Triplets conceived by ART had similar perinatal outcomes compared with spontaneously conceived triplets.
Keywords: triplet pregnancy; assisted reproductive technology; perinatal outcomes; multiple gestations